ANALISIS PENGARUH SOSIAL EKONOMI KELUARGA TERHADAP TINGKAT KECUKUPAN MINERAL KALSIUM, ZAT BESI, DAN ZINK PADA REMAJA LAKI-LAKI USIA 13—18 TAHUN DI INDONESIA - ANITA CHRISTINA SEMBIRING (CHMK HEALTH JOURNAL, 2018)
This study aims to analyze the risk factors on calsium, iron and zinc adequacy level in adolescent males age 13—18 years. A cross-sectional study was conducted using secondary data of Riskesdas 2010, with male adolescent age 13—18 years as study sample. Data on food intakes were collected with 24-hour recall method and further converted into nutrients intakes (Ca, Fe, Zn) using Food Composition Table. Nutrient adequacy level of each nutrient was calculated using Recommended Dietary Allowance. Based on the analysis of data, the prevalence of calsium and zinc deficiency in male adolescent age 13—18 years in Indonesia is still very high, 72.8% and 68.6% respectively. The prevalence of iron deficiency is still high at 51.9%. Age, father’s education, economic status and area residence are shown to affect (p<0.05) the level of adequacy of calcium, iron and zinc in adolescent malesage 13—18 years, while the level of mother’s education, father’s occupation and mother’s occupation do not.